A Study On Damage And Control Of Oryctes Rhinoceros L. (Coleoptera : Scrabaeidae) In Zero Burning Replant Oil Palm Areas Of Felda Lepar Utara, Pahang - Abidin, Cik Mohd Rizuan Zainal (2010)
A study on the implication of zero burning in the oil palm replanting program was carried out in FELDA Plantations Sdn. Bhd., Lepar Utara Complex, Pahang. Damages caused by rhinoceros beetles (RB) were assessed on different planting materials, palms of different ages, palms planted on various land topographies (hillside, hilltop, roadside, border to mature palm, swamp and valley) and various locations. Damages on oil palm trees in all topographies were not significantly different (p>0.05). The 0 - 1 year tissue cultured plants have higher damages caused by RB as compared to D x P (Dura x Pisifera).